Diabetic cardiomyopathy and COVID-19: intersecting pathways and amplified cardiovascular risk - Prakash, Swati; Choudhury, Priyanka; Bisht, Shradha (Frontiers in Pharmacology, 2025)
Diabetic cardiomyopathy (DCM) is a diabetes-induced heart condition characterized by ventricular dysfunction without other cardiac diseases. Chronic hyperglycemia, insulin resistance, and metabolic disturbances drive myocardial damage through renin–angiotensin–aldosterone system (RAAS) activation, oxidative stress, mitochondrial dysfunction, advanced glycation end product (AGE) accumulation, and persistent inflammation. The COVID-19 pandemic, caused by SARS-CoV-2, has intensified cardiovascular risk in diabetic patients. The virus uses ACE2 receptors, abundant in the heart and other organs, enabling multi-organ injury. COVID-19 may worsen glucose control or induce new-onset diabetes via pancreatic injury, insulin resistance, and stress hyperglycemia. Pre-existing diabetes increases the risk of severe COVID-19, cytokine storms, endothelial dysfunction, and thrombosis. In combination, both conditions promote RAAS imbalance, exaggerated inflammation, and hypercoagulability, amplifying myocardial injury, fibrosis, and heart failure risk. This review highlights the intricate bidirectional relationship between DCM and COVID-19, emphasizing shared pathogenic mechanisms such as RAAS dysregulation, endothelial damage, cytokine overproduction, and coagulopathy. Understanding these overlapping pathways is crucial for developing effective preventive and therapeutic strategies to mitigate adverse outcomes in this vulnerable population.